Validation of Quarter-Life Management Program Module Based on Solution-Focused Therapy - Rahman, Eva; Hasanat, Nida Ul (Faculty of Psychology, Universitas Gadjah Mada, 2025)
A quarter-life crisis is a condition related to fulfilling early adult developmental tasks. Failing to fulfil these tasks can disrupt productivity and social relationships, cause emotional instability, and increase the risks of mental disorders. The Quarter-Life Management Program Based on Solution-Focused Therapy is designed to treat individuals aged 18-25 years with quarter-life crisis who experience education, employment, social relations, or personal identity problems. This study aimed to validate the program module. The content validation procedure carried out through professional judgment, resulted in an Aiken’s V score of 0.91. The functional validation procedure was carried out through experimental research on 7 participants in experimental groups and 7 participants in waitlist-control group. The results of the within-subject test analysis indicate that the implementation of the program did not have a significant effect in reducing quarter-life crisis in the experimental group (p= 0.052). However, the program was effective in increasing a more positive self-perspective and enhancing problem-solving abilities (p= 0.035 and p= 0.007). In contrast, the waitlist-control group, which did not receive the program, showed no changes.